DETERMINAN PENCEGAHAN FRAUD PENGELOLAAN KEUANGAN DESA - Dwi Rahayu; Anim Rahmayati; Devi Narulitasari (Among Makarti, 2019)
AbstractThis study aims to determine the fraud prevention determinants of village financial management. Based on the results of the analysis and discussion, it is known that the competence of village government officials influences fraud prevention but the internal control system does not affect the prevention of fraud in village financial management in the village government of Polanharjo. This is due to the fact that there are still some village governments that have not yet separated their authority and duties because of the limited number of human resources. This research is a quantitative study using a questionnaire as a tool to obtain data. The population in this study were 18 villages in Polanharjo sub-district with a sample of 54 village government employees obtained by purposive sampling method. Keywords : fraud, kompetensi aparatur pemerintah desa, sistem pengendalian internal